2005
DOI: 10.2298/gensr0501071d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a high selection intensity on the change of maize yield components' additive variance

Abstract: A set of 31 SSD lines from ZP-Syn-1 Co and 37 from ZP-Syn-1 C3 maize population was studied in this paper. After line selection and seed multiplication in 2000, the trials were carried out in 2001-2002. at Kruševac and Zemun Polje, in RCB design. After three cycles of recurrent selection we observed a significant decrease of homozygous progenies' means of root and stalk lodged plants percent, plant and ear height, but also of row number per ear. The means of grain number per ear and 1000 grain mass were increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The excepted genetic advance was high as a percent for grain yield/plant and the value reached 20.50%. These results are in agreement with studies of Deletic et al (2005); Cook and Hallauer (2008) Hamed (2008); and . Table (6) presents estimates of heterosis for all the studied characters.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The excepted genetic advance was high as a percent for grain yield/plant and the value reached 20.50%. These results are in agreement with studies of Deletic et al (2005); Cook and Hallauer (2008) Hamed (2008); and . Table (6) presents estimates of heterosis for all the studied characters.…”
Section: Resultssupporting
confidence: 92%
“…Many researchers and plant breeders used the inbred lines of maize in diallel cross analysis (Ojo et al, 2001;Al-Sweediy, 2002;Reza'ei et al,2004;Al-Jamili ,2006 ;Chungji et al, 2006;Rather et al, 2007 and. Many studies were conducted concerning heritability for characters in different crops, Deletic et al, (2005) and Najeeb et al, (2009) obtained high heritability for the most characters, while Cook and Hallauer and Miranda (1988) and Dawod et al (2009) showed that the average dominance was less than one for all characters except the grain yield/plant, which reached 1.7. Paterniani et al (2004) found that the best expected genetic advance in grain yield reached 7.9 %.…”
Section: Introductionmentioning
confidence: 99%